Socialization of Strengthening the Role of Rural Women in Building Independent Villages and Creating Indonesia EMAS 2045: Pengabdian - Nova Ch. Mamuaya; Hajar Mukaromah; Ma’rifani Fitri Arisa; Dahlia; Bambang Amir Alhakim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The author conducted this community service through a communicative approach with village officials to involve women in various village activities. The villages in question are Kalawiran Village, Minahasa, Bajangrejo Village, Banyuurip, and Simpang Sungai Duren Village, Muaro Jambi. The conclusion in this article show that The author conducted outreach in this community service after obtaining approval from the village apparatus for women to be involved in every village activity. However, women in the village where the author conducted community service did not have high self-confidence and sufficient experience to be involved in rural activities. Based on this, the author conducted outreach to increase women's self-confidence to be involved in rural activities. There are six advantages of women compared to men in general, including the following: 1). Handle stress better. 2). Better at maintaining relationships. 3). Better at communicating. 4). Better at managing finances. 5). More capable of multitasking. 6). Have a sharper memory. These six advantages are important for women to have to improve the quality of village activities and help create independent villages. The creation of independent villages can also lead to the creation of Indonesia GOLD 2045.